Matter transfer and land use by cattle in a dehesa ecosystem of Central Spain (Vegetatio, 1992)
The transfer of matter by cattle in a 'dehesa' patureland in Central Spain has been quantified by map- ping the distribution of dung and different types of cattle behaviour in several areas distinguished by their geomorphological position, vegetation structure and management regime. Cattle show a clear preference for feeding and dung depositing in the low parts of the estate. This leads to an increase in the productivity and a rapid recycling of nutrients in the pasture communities of these areas. Comparing the relative importance of both processes in each vegetational unit, dung accumula- tion is greater in the higher zones, while in the lower areas biomass consumption is more important. This means that movement of matter by cattle tends to favour the higher ground, in a contrary direction to the downward leaching of nutrients and related processes. In the studied dehesa, this phenomena rep- resents an 'exploitation' factor of the lowland areas, which maintains productive pasture communities more immature in successional terms, by the higher woodland areas, less grazed and with low turnover. This result supports claims made in other studies that animal activity - assessed in our case by the relative impacts of herbivory and dung depositions - connect adjacent ecosystems and thus tends to improve the net energy balance of the more successionally mature part of the system. Livestock movements differ in their spatial pattern during different periods of the year: dispersing in spring and becoming more concentrated and predictable during winter. The clear seasonal differences of herbaceous production in Mediterranean climates and the management activities (basically plough- ing, tree pruning and fodder supply) are the main causes of this pattern.

Production and spatial structure of Mediterranean pastures in different stages of ecological succession (Plant Ecology, 1986)
The aim of this paper is to describe the changes of Mediterranean pasture phytomass and their dependence on succession, slope geomorphology and herbivore consumption. Four neighbouring slopes of similar aspect and steepness, located in a pasture area of Central Spain, were chosen for sampling. The slopes had not been cultivated for 1, 3, 8 and 40 years respectively. On each slope both the upper, erosion zone and the lower, accumulation zone were sampled during the months of plant growth (April to July), phytomass being record- ed in plots where herbivore consumption was avoided with protection cages and in unprotected plots. Results from the protected plots show that the upper and lower parts of slopes undergo a different develop- ment during succession. The highest values of phytomass reached, tended to decrease during succession in the upper zones, the same being true for production. However in the lower zones both parameters tended to increase in time. The ratio P/B, widely known in ecology to decrease with time, did not seem to behave as a usual index of succession in the studied ecosystem. In the upper zone this ratio tended to decrease but in the lower zone it increased with succession after the first years. Phytomass consumption by herbivores was progressively concentrated during succession in the slope sec- tors of greater production, mainly in the lower zone, which increased its productivity as the slope-talweg sys- tem became functional. The evolution of the ecological structure of a slope should be interpreted not only as a result of the tolerance of species to phsysico-chemical factors. It may also reveal the existence of an im- portant interaction between the pasture and the grazing behaviour of exploiting animals. Multivariate analy- sis of phytomass records revealed a trend of temporal variation which should be identified with the progress

Successional changes in the morphology and ecological responses of a grazed pasture ecosystem in Central Spain (Plant Ecology, 1986)
Morphological characteristics related to spatial occupation, reproduction and adaptations to grazing were used to characterize the most frequent species in a therophytic pastureland of Central Spain. Periodic ploughing is a traditional practice in these pastures and allows observation of successional change. In the present study, four neighbouring slopes of differing time since last ploughing were chosen. Species biomass was measured at different times during the annual growing season for two different slope positions. Grazing pressure is an important environmental factor affecting ecosystem organization, the most palata- ble plants tending to show increasing biomass with succession. In the most mature stages, there is a predomi- nance of species characterized by horizontal occupation of space and sprouting after mowing or grazing. During succession segregation of the different morphological characteristics occurs in slope sectors related to geomorphological dynamics. Similarly, phenological development tends to be later in pastures in the lowest slope zones, due probably to their greater summer soil moisture content.